Parameter estimation of frequency hopping signal based on time-frequency matrix LCM - Jiamin LIU; Zhijin ZHAO; Junna SHANG; Xueyi YE (Dianxin kexue)
To improve the performance of the parameter estimation of frequency hopping signal under low signal-to-noise ratio, a parameter estimation algorithm of frequency hopping signal based on time-frequency matrix LCM was proposed.Considering the different characteristics of time-frequency distribution of frequency hopping signal and noise, the mean local energy comparison value of the time-frequency matrix under different scale sliding windows was used, and the multi-scale local energy comparison feature matrix was introduced, so the time-frequency matrix P that only contains the time-frequency information of the frequency hopping signal could be obtained through this feature matrix and the adaptive threshold separation.And then, by extracting the time-frequency hopping information from P, the period, hopping time and frequency of the frequency hopping signal could be accurately estimated.The simulation results show that compared with the traditional local contrast measure (LCM) and morphological filtering method, the proposed algorithm has better frequency hopping signal extraction effect and higher parameter estimation accuracy.And then the tests of the algorithm on the DSP+FPGA hardware system verify the effectiveness and practicability.